On the Pleasure in Madness and the Grammar of Insanity - Afis, O.A. (My University, 2018)
Is madness, known in Arab-Islamic culture as al-Junun, a condition, a phenomenon or both? Is it a utopia, a dystopia and a heterotopia where the real and the unreal interpellate? To Aristotle, madness is a virtue, a quality that scholars must not only cherish but possess He says: "No great mind has ever existed without a touch of madness.” In Hamlet of Shakespeare' counsels- ‘if you must go mad, let there be a method to it”. Deeper contemplation of the problematic returns extremely rich cross-cultural tradition and cues in which contests and contestations around madness circumscribes religious, cultural, political and indeed intellectual vocations … What better example could be cited other than Gunter Grass, the German Nobel laureate in Literature who, while on his death bed, remonstrated with the medics that the only physician who could cure him of his ailment is a character he himself created in one of his works! The pursuit of the ‘pleasure’ in madness/insanity is thus conceived in the womb of time as a cultural site of meanings which only ‘mad intellectuals’, qua, al-Nasayburi and Mitchel Foucault after him, could explore particularly in an extremely ‘maddening’ world of today!
Seminar
Keywords: Arab-Islamic culture; utopia; dystopia; heterotopia; cross-cultural tradition